2014
DOI: 10.1080/17524032.2014.932819
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Theory of Planned Behavior and Media Dependency Theory: Predictors of Public Pro-environmental Behavioral Intentions in Singapore

Abstract: Applying the theory of planned behavior and media dependency theory, this study examines the effects of attitude, subjective norms, perceived behavioral control (PBC), media dependency, traditional media attention, Internet attention, and interpersonal communication on two types of pro-environmental behaviors (PEBs)-green-buying and environmental civic engagement. Regression analysis of a nationally representative survey of adult Singaporeans (N = 1168) indicated that attitude, PBC, media dependency, tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 69 publications
8
150
0
5
Order By: Relevance
“…Given that assumption, planned behaviors are inherently knowledge-based. That argument is consistent with previous findings that attention to pro-environmental media messages is positively related to pro-environmental behavioral intention [29]. Whereas previous research has associated perceived knowledge about a behavior with attitude toward the behavior [35], the current study suggests that an important component of behavior has to do with procedural knowledge and its relation to perceived behavioral control.…”
Section: Theoretical Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…Given that assumption, planned behaviors are inherently knowledge-based. That argument is consistent with previous findings that attention to pro-environmental media messages is positively related to pro-environmental behavioral intention [29]. Whereas previous research has associated perceived knowledge about a behavior with attitude toward the behavior [35], the current study suggests that an important component of behavior has to do with procedural knowledge and its relation to perceived behavioral control.…”
Section: Theoretical Implicationssupporting
confidence: 77%
“…Although attitude is not the same as intention or behavior, it is an important antecedent of both, and that finding suggests that useful information may indirectly facilitate behavior. Another study found that individuals who report using the media in order to better understand how to deal with environmental issues have stronger pro-environmental behavioral intention [29]. In other words, individuals who seek useful action-related information have stronger motivation to engage in related behaviors.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…Researchers find that televised public affairs news and nature documentaries positively predict people's pro-environmental behavior (Holbert, Kwak, & Shah, 2003). Media variables including traditional media and Internet attention also positively predict green purchasing and environmental civic engagement, respectively (Ho, Liao, & Rosenthal, 2015). In addition, newspapers and web use have an impact on environmental information seeking through environmental knowledge (Zhao, 2009).…”
Section: Media Use and Pro-environmental Behaviormentioning
confidence: 95%
“…TPB has been broadly used to identify determinants of environmental behaviours, such as buying green products (Ho, Liao, and Rosenthal 2014), recycling (Wan, Shen, and Yu 2014), purchasing eco-friendly phones (Paladino and Ng 2012), consuming sustainable food (Han and Hansen 2012) and saving household energy (Abrahamse and Steg 2009).…”
Section: Environmental Behavioural Theorymentioning
confidence: 99%
“…However, existing online calculators, which apply no environmental behavioural theory, provide a mere calculation function, thereby having limited influence on their users. Environmental behavioural theories argue that the determinants of an individual's environmental behaviour include his/her knowledge, awareness, attitude, behavioural control and social norms (Gatersleben, Steg, and Vlek 2002;Ho, Liao, and Rosenthal 2014;Lim et al 2013;Wan, Shen, and Yu 2014). Therefore, this study attempted to construct a new system grounded on the theories.…”
Section: Introductionmentioning
confidence: 98%